Nusantara : Sejarah Indonesia / Bernard H. M. Vlekke; Penerjamah, Samsudin Berlian; Penyunting, Zaim Rofiqi, Mardi Siswoko Baktii - Vlekke, Bernard H.M. ; Samsudin Berlian ; Zaim Rofiqi ; Mardi Siswoko Bakti (KPG (Kepustakaan Populer Gramedia ), 2016)
xxi, 440 hlm. : ilus. ; 23 cm.